Guardiani della memoria. Il Comitato onoranze e ricerche caduti nell’Eritrea del secondo dopoguerra - Nicholas Lucchetti (Storia e Futuro, 2022)
The article describes the activity of an italian committee created in Eritrea after the Second World War to dealing with War graves and tracing the missing. Using journalistic sources (particularly the Italian press published in Asmara), documents and the results of historiography, the article analyzes the committe’s action in the Eritrean context, between political struggle and international debates on the fate of the territory. The committee was an important emanation of the Italian community; it celebrated the story of the ex colonial soldiers and worked to construct an orphanage in Adi Quala.